PENGARUH CURRENT RATIO DAN DEBT TO EQUITY RATIO TERHADAP RETURN ON ASSET PADA PT ADI SARANA ARMADA TBK PERIODE 2014–2024 - Devi Andela; Iman Lubis (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study aims to analyze the effect of Current Ratio and Debt to Equity Ratio on Return on Assets at PT Adi Sarana Armada Tbk during the 2014–2024 period. The research method used is a quantitative method with a descriptive and verification approach. The data used are secondary data obtained from the company's annual financial statements. Data analysis techniques used include descriptive statistical analysis, classical assumption tests, multiple linear regression analysis, and hypothesis testing using t-tests, F-tests, and coefficients of determination (R²) with the help of the SPSS version 26 program. The results of the study indicate that partially the Current Ratio does not have a significant effect on Return on Assets, which is indicated by a significance value of 0.925 > 0.05. Similarly, Debt to Equity Ratio partially also does not have a significant effect on Return on Assets with a significance value of 0.771> 0.05. Simultaneously, the Current Ratio and Debt to Equity Ratio do not significantly influence Return on Assets, with a significance value of 0.904 > 0.05 and an Fcount value < Ftable. In addition, the Adjusted R Square value of -0.219 indicates that the ability of the independent variables to explain variations in Return on Assets is very low.